Análise do comportamento do consumidor, previsão de demanda utilizando regressão linear. - Assis, Claudemir Pedro Simão de (Universidade Federal do Tocantins, 2020)
This article about the research conducted in the years 2013, 2014 and 2015, the socioeconomic profile of the consumers of the municipality of Araguaína-TO in the main commemorative dates, Mother's Day, Valentine's Day and Father's Day. The objective is to perform a demand forecast for the year 2017 using a linear regression method. The method chosen for linear regression using an EXCEL 2010 tool, for handling the collected data. The survey was conducted in the years of 2013 to 2015, where 3604 consumers were interviewed. As theoretical reference was used consumer behavior, targeted marketing, SWOT analysis and demand forecasting. The data were organized into tables describing the year and consumer behavior on the major commemorative dates and the data were made a demand forecast for the year 2017, which is of the utmost importance for companies to be able to forecast their future inventories E With this to outline their strategies to satisfy the consumer.Linear regression is a method of forecasting demand that there may be variables that may compromise the end result. It was verified that a reliability of the forecast of demand for the year 2017, found in this work is above the standards acceptable in the literature, being able to have as main fact or short term of data collection, that only three years. Therefore, work of extreme relevance, but should be the subject of a more continuous study.